Congestion Management by Optimal Generation Rescheduling Using Sine Cosine Algorithm - Kumar Tailor, Tarun; Kumar, Yogendra; Dubey, Manisha (International Journal of Engineering and Technology, 2018)
Under deregulated market environment, technically efficient and cost-effective operation of the power system becomes imperative. Congestion in transmission lines is one among key facet dealt by network operator as it greatly affects the operation of power system. This paper intends to manage power network congestion by means of rescheduling real power generation. Sensitivity analysis has been carried out to select the generators for rescheduling real power generation. In order to improve the economic efficiency of the electrical power market, an attempt is made to minimize the congestion cost. Sine Cosine Algorithm (SCA) has been employed to solve the considered problem. The viability of the considered method has been investigated by implementing it on the modified IEEE 57-bus test system. To confirm the efficacy of employed algorithm obtained results are compared with those available in the literature. The results illustrate that considered approach offers improved results and effectively minimizes congestion cost.Â Â Â
Keywords: Congestion Management; Generation Rescheduling; Optimal Power Flow; Sine Cosine Algorithm.